Qanun Aceh No 14 Tahun 2003 Tentang Khalwat Dalam Pandangan Fik{ih dan KUHP - Ali Geno Berutu (Muslim Heritage, 2017)
Abstract: Interdiction of khalwat (seclusion) is the early prevention of fornication, because it is basically starts from the things that lead to it. The establishment of Qanun No. 14 of 2003 on khalwat (seclusion) as Qanun in jinayat in the early application of Islamic law in Aceh is not without reason, that selection has at least two reasons. The first reason, khalwat (seclusion) is the one form of immoral deed (haram) in Islamic law and very disturbing on society. The second reason, there is euphoria on society in the form of "people's justice" to this Qanun in jinayat. Therefore in order to avoid any vigilante among society in Aceh, Aceh Government established Qanun No. 14 of 2003 to anticipate any chaos among society in Aceh. Abstrak: Larangan khalwat merupakan pencegahan dini terhadap perbuatan zina karena perbuatan zina pada dasarnya dimulai dari hal-hal yang mengarah kepadanya. Pengesahan Qanun No 14 Tahun 2003 tentang Khalwat pada awal penerapan syariat Islam di Aceh sebagai qanun dalam bidang jina>ya>t bukannya tanpa alasan, pemilihan qanun tersebut sekurang-kurangnya memiliki dua alasan. Alasan yang pertama, perbuatan khalwat mmerupakan bentuk maksiat (haram) dalam syariat Islam dan sangat meresahkan masyarakat namun belum tertangani dengan baik. Kedua, adanya euforia di dalam lapisan masyarakat dalam bentuk “peradilan rakyat” terhadap jenis yang diatur dalam qanun jina>ya>t ini, guna untuk menghindari main hakim sendiri ditengah-tengah masyarakat, maka Pemerintah Aceh mengesahkan Qanun No 14 Tahun 2003 sebagai bentuk antisipasi terhadap berbagai kekacauan di lapisan masyarakat Aceh.